DEVELOPMENT OF A RECOMBINANT VACCINE TO PREVENT INFLUENZA VIRUS INFECTION - Loso Judijanto; Aung Myint; Nandar Hlaing; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2025)
Influenza virus remains a significant global health challenge, causing seasonal epidemics and potential pandemics with high morbidity and mortality rates. This study aims to develop a recombinant vaccine as a safer and more effective alternative to traditional influenza vaccines, which often suffer from limited efficacy and lengthy production timelines. Utilizing a recombinant DNA technology approach, this research employed the baculovirus expression system to produce hemagglutinin (HA) antigens derived from the influenza A virus. Experimental methods included antigen purification, immunogenicity assays in murine models, and neutralizing antibody titration. Results revealed that the recombinant HA vaccine elicited a robust immune response, with a significant increase in hemagglutination inhibition titers compared to control groups. Furthermore, the vaccinated subjects exhibited substantial protection against viral challenge, evidenced by reduced viral load and minimized lung pathology. The findings suggest that recombinant vaccine platforms offer promising avenues for rapid and scalable vaccine development. This study underscores the potential of recombinant influenza vaccines in mitigating future influenza outbreaks with improved safety, efficacy, and production agility.